PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PERJANJIAN PAYLATER PADA E-COMMERCE DI INDONESIA - Machmuda Aghisna; Rahmatullah Ayu Hasmiati (LPPM STIH Awang Long, 2026)
The development of financial technology in the e-commerce sector has given rise to an innovative digital credit-based payment system known as PayLater. While this instrument offers convenience for consumers to conduct transactions without immediate payment, it raises legal issues regarding contractual agreements, the use of standard clauses, and consumer legal protection from a civil law perspective. The imbalance in the bargaining position of the parties within electronic agreements is the primary reason for conducting this study, considering that PayLater has become an integral part of the modern financing system widely utilized in Indonesian digital trade practices. This study employs a normative legal research method with a statutory approach and a conceptual approach. The legal materials used consist of primary legal materials in the form of laws and regulations related to civil law, consumer protection, and electronic transactions, as well as secondary legal materials comprising legal literature, scientific journals, and expert doctrines. The analysis technique is carried out qualitatively through legal interpretation of prevailing norms to assess the conformity between legal regulations and the practice of PayLater agreements in e-commerce. The results of the study indicate that PayLater constitutes a valid form of electronic-based loan agreement under Indonesian civil law, provided it meets the requirements of Article 1320 of the Indonesian Civil Code (KUHPerdata) and is recognized under the Law on Electronic Information and Transactions (UU ITE). Nonetheless, agreement practices reveal a dominance of standard clauses that create an imbalance of position between business actors and consumers. The study concludes that legal protection for consumers in PayLater agreements is normatively regulated, yet it still requires strengthening in aspects of implementation, information transparency, and supervision to guarantee equity between the parties in digital transactions.